Analisis Strategi Bauran Pemasaran (7) Gojek Dalam Memberikan Harga Lebih Terjangkau Bagi Konsumen Melalui Website Resmi - Azzahra, Salsa Dilla; Lutfi Vanisa Aulia,; Helin Garlinia Yudawisastra, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2026)
The development of digital technology has intensified competition in the online transportation industry, requiring companies to adopt effective marketing strategies. This study analyzes the application of the 7P marketing mix by PT Gojek Indonesia in shaping the perception of affordable prices through its official website. The research method used is descriptive qualitative with literature review and documentation, utilizing secondary data from Gojek’s official website and related sources. The findings show that Gojek consistently integrates all elements of the 7P marketing mix, including service diversification, transparent pricing through dynamic pricing, omnichannel distribution, digital promotion, driver quality, technology-based processes, and physical evidence such as visual identity and security systems. These strategies contribute to creating a competitive price perception, despite the implementation of surge pricing during certain periods. In conclusion, the 7P marketing mix plays a crucial role in maintaining price affordability and strengthening Gojek’s competitiveness in the online transportation industry.